Non‐Pt Nanostructured Catalysts for Oxygen Reduction Reaction: Synthesis, Catalytic Activity and its Key Factors. Issue 17 (25th July 2016) - Xia, Zhonghong; An, Li; Chen, Peikai; Xia, Dingguo
Abstract : Pt‐based electrocatalysts for the oxygen reduction reaction (ORR) are the topic of extensive and intensive research since a few decades. Nevertheless, the scarcity of these Pt‐based electrocatalysts, their high cost and unsatisfactory durability are the primary hindrances to their further commercialization. In recent years, non‐Pt electrocatalysts have garnered considerable interest as alternatives to Pt‐based catalysts for the ORR. This review highlights the synthesis, catalytic activity and key factors, namely also active sites, of various nanostructured non‐Pt catalysts that can be grouped into five categories: monometallic catalysts; bimetallic or multimetallic catalysts; transition metal oxides/chalcogenides/nitrides/oxynitrides/carbides; heteroatom‐doped carbon catalysts with and without transition metals and metal–organic frameworks (MOFs)‐derived catalysts that have emerged as a class of promising catalysts recently. For metallic catalysts, the ORR activity and durability can be tuned by capitalizing on such effects as surface ligands and lattice strain; for heteroatom‐doped carbon catalysts, some factors like mass transport and electric conductivity are nontrivial for enhancement of the ORR activity. Recent research advances are presented and an outlook for future research is provided. Abstract : Recent progress on oxygen reduction reaction (ORR) electrocatalysts used in proton‐exchange‐membrane fuel cells (PEMFCs) is presented, including monometallic catalysts, bimetallic or multimetallic catalysts, transition metal oxides, chalcogenides, nitrides, oxynitrides and carbides, heteroatom‐doped carbon materials with and without transition metals, and metal–organic frameworks (MOFs)‐derived catalysts. Key factors are demonstrated to improve ORR catalytic activities.